2014
DOI: 10.1016/j.febslet.2014.05.067
|View full text |Cite
|
Sign up to set email alerts
|

A feedback regulatory loop between HIF‐1α and miR‐21 in response to hypoxia in cardiomyocytes

Abstract: Edited by Tamas DalmayKeywords: Hypoxia Hypoxia-inducible factor 1a (HIF-1a) MicroRNA miR-21 Cardiomyocytes a b s t r a c t Accumulating evidence suggests that hypoxia-inducible factor 1a (HIF-1a) regulates numerous miRNAs and is crucial for cellular response to hypoxia. However, the relationship between HIF-1a and miR-21 in hypoxic cardiomyocytes is little known. We found that hypoxia induced HIF-1a and miR-21 expression. HIF-1a knockdown increased cell apoptosis and reduced miR-21 expression. Furthermore, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 42 publications
2
66
0
Order By: Relevance
“…Certain miRNAs, including those examined here, have been implicated in the regulation of VEGF expression. [91718] This observation is also supported by other data. For instance, overexpressing miR-210 in HUVECs can promote angiogenesis through upregulation of VEGF and VEGFR-2.…”
Section: Discussionsupporting
confidence: 87%
“…Certain miRNAs, including those examined here, have been implicated in the regulation of VEGF expression. [91718] This observation is also supported by other data. For instance, overexpressing miR-210 in HUVECs can promote angiogenesis through upregulation of VEGF and VEGFR-2.…”
Section: Discussionsupporting
confidence: 87%
“…In accord, Csn5 deficiency decreased and MLN4924 stabilized HIF-1α in LPS-elicited macrophages (and endothelial cells). Both miR-146a and -21a expression levels are coregulated by HIF-1α (55,56). Decreased miR-21 and -146a levels in Csn5-deficient macrophages might thus in part be explained by reduced HIF-1α transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 shows features of oncomirs by targeting many tumor suppressor genes related to cell proliferation, apoptosis, and invasion in multiple histologic types of cancer, including OSCC (42,43). Recently, studies have demonstrated that hypoxia induces miR-21 expression in a HIF-1a-dependent manner in pancreatic cancer cells (44) and cardiomyocytes (36). In contrast, in renal cancer, it has been suggested that the dysregulation of miR-21 is HIF-independent (45).…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted and PCR was performed with primers for a miR-21 promoter fragment containing a HIF response element (HRE; ref. 36). Primers that amplify a region in the promoter of miR-130b were used as a negative control (37).…”
Section: Chromatin Immunoprecipitation Assaymentioning
confidence: 99%